Behavioural and neural evidence for self-reinforcing expectancy effects on pain. (November 2018) - Jepma, Marieke; Koban, Leonie; Doorn, Johnny; Jones, Matt; Wager, Tor
Abstract Beliefs and expectations often persist despite evidence to the contrary. Here we examine two potential mechanisms underlying such 'self-reinforcing' expectancy effects in the pain domain: modulation of perception and biased learning. In two experiments, cues previously associated with symbolic representations of high or low temperatures preceded painful heat. We examined trial-to-trial dynamics in participants' expected pain, reported pain and brain activity. Subjective and neural pain responses assimilated towards cue-based expectations, and pain responses in turn predicted subsequent expectations, creating a positive dynamic feedback loop. Furthermore, we found evidence for a confirmation bias in learning: higher- and lower-than-expected pain triggered greater expectation updating for high- and low-pain cues, respectively. Individual differences in this bias were reflected in the updating of pain-anticipatory brain activity. Computational modelling provided converging evidence that expectations influence both perception and learning. Together, perceptual assimilation and biased learning promote self-reinforcing expectations, helping to explain why beliefs can be resistant to change. Jepma and colleagues provide evidence that prior beliefs about pain influence perceived intensity of pain, and the degree of learning about pain intensity. This finding helps to explain why beliefs are often resistant to updating with experience.